Prospective validation of a biomarker-driven response prediction model to romiplostim in lower-risk myelodysplastic neoplasms: results of the EUROPE trial by EMSCO : myelodysplastic neoplasms - Kubasch, Anne Sophie; Giagounidis, Aristoteles; Metzgeroth, Georgia; Jonasova, Anna; Herbst, Regina; Diaz, Jose Miguel Torregrosa; De Renzis, Benoit; Götze, Katharina; Huetter-Kroenke, Marie-Luise; Gourin, Marie-Pierre; Slama, Borhane; Dimicoli-Salazar, Sophie; et al. (Leukemia, 2022)
The EUROPE phase 2 trial investigated the predictive value of biomarkers on the clinical efficacy of single agent romiplostim (ROM) treatment in patients with lower-risk myelodysplastic neoplasms (LR-MDS) and thrombocytopenia within the ‘European Myelodysplastic Neoplasms Cooperative Group‘ (EMSCO) network. A total of 77 patients with LR-MDS and a median platelet count of 25/nl were included, all patients received ROM at a starting dose of 750 μg by SC injection weekly. Thirty-two patients (42%) achieved a hematologic improvement of platelets (HI-P) with a median duration of 340 days. Neutrophil (HI-N) and erythroid (HI-E) responses were observed in three (4%) and seven (9%) patients, respectively. We could not confirm previous reports that HI-P correlated with baseline endogenous thrombopoietin levels and platelet transfusion history, but SRSF2 mutation status and hemoglobin levels at baseline were significantly linked to HI-P. Sequential analysis of variant allelic frequency of mutations like SRSF2 did not reveal an impact of ROM on clonal evolution in both responders and non-responders. In summary, our study confirms the safety and efficacy of ROM in LR-MDS patients and may allow to better define subgroups of patients with a high likelihood of response.
Gesehen am 14.08.2023